A contribution to the research of children protection in use of Internet - Nebojša Denić; Zoran Nešić; Miroslav Radojičić; Dalibor Petković; Mališa Stevanović (Tehnički Vjesnik, 2017)
The main aim of this paper is to study the current state of children protection in their use of the Internet. The research includes a consideration of the factors influencing the protection of children from various aspects, based on the test results of the children, their parents and teachers. The results suggest a pronounced influence of the specific social circumstances of the environment in which the research study was conducted. With regard to the education of children, where schools and teachers play an important role, the paper highlights the importance of professional and methodical applicable IT education at educational institutions, the use of new information technologies in education, with an emphasis on the threats on the Internet, security on the Internet, the prevention of violence on the Internet, the rights of children on the Internet and the rules for a safe Internet use in relation to age. This study was carried out on the example of a case study.